Faktor Faktor Yang Berhubungan Dengan Kejadian Persalinan Preterm Di Ruang Bersalin Puskesmas Kecamatan Tambora Tahun 2023 - eni marfuah; Irene Florensia Situmeang; Delvira Andini (Politeknik Karya Husada, 2024)
Factors Associated with Preterm Birth Incidence in the Delivery Room of Tambora Sub-District Public Health Center in 2023. According to WHO, approximately 13.4 million babies were born prematurely in 2020. Premature birth is a leading cause of death among children under 5 years old, accounting for about 900,000 deaths in 2019. Worldwide, the prevalence of premature births ranges from 4% to 16% in 2020. In Indonesia, the neonatal mortality rate is 16.85 per 1,000 live births. Jakarta experienced a decrease in infant mortality rates by 92% during the period 1971-2020. However, the infant mortality rate declined from 14 to 10-11 per 1,000 live births between the 2010 and 2020 population censuses. The causes of preterm birth remain uncertain, as premature birth can occur for various reasons. This research was conducted in Tambora District Health Center in 2023 with the aim of identifying factors associated with preterm birth. The study employed a case-control approach, involving 40 cases of preterm birth and 40 controls of full-term births. The bivariate analysis results revealed that age (p = 0.309, OR 1.926) and nutritional status (p = 0.642, OR 1.385) did not show a significant relationship with preterm birth incidence. However, a significant association was found between premature rupture of membranes (PROM) and preterm birth incidence (p = 0.000, OR 19.000). Based on the research findings, it is recommended that healthcare professionals provide education on regular prenatal check-ups to prevent infections that could lead to PROM and other factors related to preterm birth. Ensuring proper nutrition for pregnant mothers and paying attention to safe gestational age are also considered essential. Through these interventions, the rate of preterm births is anticipated to be further reduced. Keywords: age, nutritional status, preterm birth, premature rupture of membranes (PROM)..